Math, asked by sachinkumar825, 1 year ago

simplify the expression under bracket 4 root 5 minus 3 root 2 bracket close bracket 3 root 5 + 5 root 2 bracket close

Attachments:

Answers

Answered by mysticd
46

Answer:

30+1110

Explanation:

Simplification of

(45-32)(3√5+5√2)

=45(3√5+5√2)-32(3√5+5√2)

= 60+20√10-9√10-30

= 60-30+(20-9)√10

= 30+11√10

Therefore,

(4√5-3√2)(3√5+5√2)

= 30+11√10

••••

Answered by akshdalal2006
3

Answer: )( 4root5-3root2) (3root +5root2) = 4root5(3root5+5root2) -3root2(3root5+5root2)=60+20root10-9root10-30 =30+11root10 Ans

Similar questions